Prion diseases: dynamics of the infection and properties of the bistable transition. - Kellershohn, N (2001)
Prion diseases are thought to result from a pathogenic, conformational change in a cellular protein, the prion protein. The pathogenic isoform seems to convert the normal isoform in an autocatalytic process. In contrast to the conditions used for in vitro studies of enzyme kinetics, the concentration of the catalyst is not much lower than that of the substrate in the course of infection. This feature may endow the system with a time-hierarchy allowing the pathogenic isoform to relax very slowly in the course of infection. This may contribute to the long incubation periods observed in prion diseases. The dynamic process of prion propagation, including turnover of the cellular prion protein, displays bistable properties. Sporadic prion diseases may result from a change in one of the parameters associated with metabolism of the prion protein. The bistable transition observed in sporadic disease is reversible, whereas that observed in cases of exogenous contamination is irreversible. This model is consistent with the occurrence of rare, sporadic forms of prion diseases. It may also explain why only some individuals of a cohort develop a prion disease following transient food contamination.